Women on their own : interdisciplinary perspectives on being single - Bell, Rudolph M.; Yans-McLaughlin, Virginia, 1943- (Book collections on Project MUSE., 2008)
"This collection of eleven original essays attempts to present a more complex view of single women. The writers embrace a broad definition of singleness, one that includes women who never married, those who co-habit but are legally denied the right to marry, divorcees, and widows. They describe women who defiantly voted in political elections, single mothers who rejected dependency on public assistance programs, women who successfully ran businesses, and others who found fulfillment in charitable work. Collectively, the self-reliance, creativity; and power to redefine difficult situations that these women demonstrate make a powerful statement about the successes of women on their own."--Jacket.